Flour water salt yeast : the fundamentals of artisan bread and pizza - Forkish, Ken (Ten Speed Press, 2012)
"From Portland's most acclaimed and beloved baker comes this must-have baking guide, featuring scores of recipes for world-class breads and pizzas and a variety of schedules suited for the home baker. In Flour Water Salt Yeast, author Ken Forkish demonstrates that high-quality artisan bread and pizza is within the reach of any home baker. Whether it's a basic straight dough, dough made with a pre-ferment, or a complex levain, each of Forkish's impeccable recipes yields exceptional results. Tips on creating and adapting bread baking schedules that fit in reader's day-to-day lives--enabling them to bake the breads they love in the time they have available--make Flour Water Salt Yeast an indispensable resource for bakers, be they novices or serious enthusiasts"--